Development and validation of an epitope-blocking ELISA using an anti-haemagglutinin monoclonal antibody for specific detection of antibodies in sheep and goat sera directed against peste des petits ruminants virus - (:unkn) unknown (My University, 2018)
Peste des petits ruminants (PPR) is a contagious and economically important disease affecting production of small ruminants (i.e., sheep and goats). Taking into consideration the lessons learnt from the Global Rinderpest Eradication Programme (GREP), PPR is now targeted by the international veterinary community as the next animal disease to be eradicated. To support the African continental programme for the control of PPR, the Pan African Veterinary Vaccine Centre of the African Union (AU-PANVAC) is developing diagnostics tools. Here, we describe the development of a blocking enzyme-linked immunosorbent assay (bELISA) that allows testing of a large number of samples for specific detection of antibodies directed against PPR virus in sheep and goat sera. The PPR bELISA uses an anti-haemagglutinin (H) monoclonal antibody (MAb) as a competitor antibody, and tests results are interpreted using the percentage of inhibition (PI) of MAb binding generated by the serum sample. PI values below or equal to 18% (PI ae<currency> 18%) are negative, PI values greater than or equal to 25% (PI ae<yen> 25%) are positive, and PI values greater than 18% and below 25% are doubtful. The diagnostic specificity (DSp) and diagnostic sensitivity (DSe) were found to be 100% and 93.74%, respectively. The H-based PPR-bELISA showed good correlation with the virus neutralization test (VNT), the gold standard test, with a kappa value of 0.947. The H-based PPR-bELISA is more specific than the commercial kit ID ScreenA (R) PPR Competition (N-based PPR-cELISA) from IDvet (France), but the commercial kit is slightly more sensitive than the H-based PPR-bELISA. The validation process also indicated good repeatability and reproducibility of the H-based PPR-bELISA, making this new test a suitable tool for the surveillance and sero-monitoring of the vaccination campaign.
Keywords: African Research